2016
DOI: 10.1080/15459624.2015.1116698
|View full text |Cite
|
Sign up to set email alerts
|

Capture of 0.1-μm aerosol particles containing viable H1N1 influenza virus by N95 filtering facepiece respirators

Abstract: Nosocomial infections pose an escalating threat to both patients and healthcare workers (HCWs). A widely recommended device for individual respiratory protection, the N95 filtering facepiece respirator (FFR) has been shown to provide efficient filtration of inert particles larger and smaller than the nominal most-penetrating particle size (MPPS) range, 0.03-0.3 μm. Humans generate respiratory aerosols in the MPPS range, suggesting that short-range disease transmission could occur via small infectious particles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…[39] Another study generated an aerosol CMD of ∼0.1 µm using viable H1N1 influenza to challenge N95 FFRs. [44] Thus, if there was interest, more challenging VFE methods could be developed by a standards development organization, although a modified VFE with an aerosol challenge in the MPPS range would still be considered unnecessary for determining FFR efficacy as noted previously. [44] The VFE method used in this study is adapted from the ASTM F2101 standard and is not being recognized by standard organizations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[39] Another study generated an aerosol CMD of ∼0.1 µm using viable H1N1 influenza to challenge N95 FFRs. [44] Thus, if there was interest, more challenging VFE methods could be developed by a standards development organization, although a modified VFE with an aerosol challenge in the MPPS range would still be considered unnecessary for determining FFR efficacy as noted previously. [44] The VFE method used in this study is adapted from the ASTM F2101 standard and is not being recognized by standard organizations.…”
Section: Discussionmentioning
confidence: 99%
“…[44] Thus, if there was interest, more challenging VFE methods could be developed by a standards development organization, although a modified VFE with an aerosol challenge in the MPPS range would still be considered unnecessary for determining FFR efficacy as noted previously. [44] The VFE method used in this study is adapted from the ASTM F2101 standard and is not being recognized by standard organizations. VFE method used in this study should not be considered useful for characterizing filter material efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…This similarity in filtration efficiency for different size microbes may reflect, in large part, the fact that the challenge was in the form of aerosol particles with MPS of ~3.0 μm. The particle size used was that stipulated in the relevant Standard (ASTM F2101) (12,13) and reflects the concern over transmission of infectious agents through fine aerosols, as has been demonstrated for influenza virus (25)(26)(27) and smallpox (variola) virus (28). The potential role of fine aerosols in transmission of a variety of viruses, such as measles, influenza, rhinoviruses, severe acute respiratory syndrome coronavirus (SARS-CoV), Middle East respiratory syndrome coronavirus (MERS-CoV), hantavirus (Sin Nombre virus), rabies, pox and Ebola viruses has been reviewed (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…The cloth facemasks, depending on the type of fabrics, is reported to have virus (bacteriophage MS2) filtering efficiency of 50‒70% ( Davies et al, 2013 ). The virus filtering efficiency of three ply SMS (Spun bonded–Melt blown–Spun bonded) type surgical masks and N95 respirators was reported to be 85‒95%( Balazy et al, 2006 ; Davies et al, 2013 ) and 95‒97% ( Balazy et al, 2006 , p. 95; Harnish et al, 2016 ; Rengasamy et al, 2017 ; Zhou et al, 2018 ), respectively. A cluster randomized trial study on the effectiveness of cloth masks ( Davies et al, 2013 ), medical masks ( Leung et al, 2020 ) and respirators ( Radonovich et al, 2016 ) in hospital settings was also reported.…”
Section: Introductionmentioning
confidence: 99%